Pengaruh Pengungkapan Emisi Karbon dan Annual Report Readability terhadap Nilai Perusahaan - Willy Dozan Alfayerds; Mia Angelina Setiawan (Universitas Negeri Padang, 2021)
The objevtive of this study is to investigate the influence of carbon emissions disclosure and annual report readability on firm value. The sampel consist of firms that listed in PROPER’s and Indonesian Stock Exchange (BEI) for the year (2016-2018). By using multiple regression analysis, the results show that carbon emissions disclosure has a positive influence on firm value, while it has no significant influence with annual report readability. This study contributes to the accounting field in maximizing the role to tackle the climate change and global warming.